1985
DOI: 10.1530/jrf.0.0750369
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation after sympathetic denervation of the rat ovary produced by freezing its nerve supply

Abstract: Summary. The ovaries of cyclic female rats were unilaterally or bilaterally denervated or sham-operated. Denervation was achieved by freezing the ovarian vascular pedicle and suspensory ligament about 1 cm from the ovary; this technique renders the ovary devoid of innervation for up to 10 days. Denervated ovaries from 6 unilaterally and 7 bilaterally operated animals exhibited normal ovulation rates (5\m=.\8\ m=+-\1\m=.\0and 5\m=.\2\ m=+-\1\ m=. \ 2 respectively, mean \m=+-\ s.e.m.) compared with intact (5\m=.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In earlier studies we showed that brief freezing of the ovarian nerve supply produces complete adrenergic denervation of the ovary and the oviduct (Gibson, Roche, Summers & Wylie, 1984) but does not interfere with ovulation (Wylie, Roche & Gibson, 1985). In the present study we extend this work to test whether pregnancy can be initiated and maintained and whether normal parturi¬ tion can occur when the adrenergic innervation of the ovary, oviduct, mesosalpinx, utero-tubal junction and upper uterine horn is eliminated.…”
Section: Introductionsupporting
confidence: 54%
“…In earlier studies we showed that brief freezing of the ovarian nerve supply produces complete adrenergic denervation of the ovary and the oviduct (Gibson, Roche, Summers & Wylie, 1984) but does not interfere with ovulation (Wylie, Roche & Gibson, 1985). In the present study we extend this work to test whether pregnancy can be initiated and maintained and whether normal parturi¬ tion can occur when the adrenergic innervation of the ovary, oviduct, mesosalpinx, utero-tubal junction and upper uterine horn is eliminated.…”
Section: Introductionsupporting
confidence: 54%
“…The relation between ovulation and ovarian innervation has also been discussed (Bahr et al, 1974) and it has been suggested that there is no direct relation between them (Wylie et al, 1985). However, the intrabursal application of norepinephrine and adrenergic agonists and antagonists in the ovary showed a significant increase in the number of new corpora lutea in prepuberal rats primed with PMSG (Kannisto et al, 1985).…”
Section: Innervation and Ovarian Functionmentioning
confidence: 99%
“…There are numerous reviews and articles on sperm transport in the female genital tract [16,27,28] and the main objective with the transport is obviously to establish a population of fertilizable or viable spermatozoa near the oocyte prior to the process of ovulation by inducing contraction of the follicular wall prior to the collapse of the preovulatory follicle [43]. Other studies have, however, shown that denervation of the ovary has no adverse effect on the ovulatory process so the effect of the nervous system is still not clear [58]. The duration of the ovulatory process is estimated to be approximately 6 min in the mare [55], 1.8 h in pigs [50] and 4-12 h in the superovulated cow [3,4].…”
Section: The Spermatozoamentioning
confidence: 99%